Whole Genome Low-Coverage Sequencing Concurrently Detecting Copy Number Variations and Their Underlying Complex Chromosomal Rearrangements by Systematic Breakpoint Mapping in Intellectual Deficiency/Developmental Delay Patients - Xiao, Bing; Ye, Xiantao; Wang, Lili; Fan, Yanjie; Gu, Xuefan; Ji, Xing; Sun, Yu; Yu, Yongguo (Frontiers in Genetics, 2020)
Simple copy number variations (CNVs) detected by chromosomal microarray (CMA) can result from complex structural changes. Therefore, it is necessary to characterize potential structural changes that cause pathogenic CNVs. We applied whole-genome low-coverage sequencing (WGLCS) to concurrently detect pathogenic CNVs and their associated chromosomal rearrangements in 15 patients. All the patients had an average of 2–3 pathogenic CNVs involving 1–2 chromosomes. WGLCS identified all the 34 pathogenic CNVs found by microarray. By identifying chimeric read pairs, WGLCS mapped 70 breakpoints in these patients, of which 47 were finely mapped at the nucleotide level and confirmed by subsequent PCR amplification and Sanger sequencing of the junction fragments. In 15 patients, structural rearrangements were defined at molecular level in 13 patients. In 13 patients, WGLCS reveal no additional results in two patients. In another eleven patients, WGLCS revealed new breakpoints or finely mapped the genes disrupted by breakpoints or 1-6bp microhomology and/or short insertion (4-70bp) in the breakpoints junctions. However, structural changes in the other two patients still remained unclear after WGLCS was performed. The structural alteration identified in the 13 patients could be divided into the following categories: (1) interstitial inverted duplication with concomitant terminal deletion (inv dup del) (P1,P4,P9,P11); (2) the product of pericentric inversion (P5); (3) ring chromosome (P8); (4) interstitial duplication and/or triplication (P6, P7); and (5) +der(22)t(11;22) (P2,P15); (6) complex structural rearrangements (P3,P12,P14). WGLCS displayed the ability to discover CNVs and define breakpoints and its disrupted genes and its surrounding sequences in one experiment at base-pair-resolution, which help us to learn more about the mechanisms of formation of observed genomic rearrangements, and in which DNA replicative/repair mechanism might contribute to the formation of complex rearrangements in 11 patients. Clear karyotype at molecular level could help provide an accurate evaluation of recurrent risk and guide prenatal diagnosis or reproductive planning.